Intervensi Edukasi Untuk Meningkatkan Self Efficacy dan Mengontrol IDWG Pada Pasien Hemodialisa: Narrative Review - Sulistiyowati, Sulistiyowati; Winarto, Eko (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Introduction: The main problem of patients undergoing hemodialysis is Inter Dialytic Weight Gain (IDWG). The patient's inability to follow a CKD diet is influenced by low self-confidence or self-efficacy. Patients need effective education so that patients can increase their self-efficacy to maintain IDWG. Objectives: This study aims to determine the effect of educative intervention on Self-Efficacy and Interdialytic Weight Gain (IDWG) Values in CKD Patients Undergoing Hemodialysis. Research Methods: This research is a narrative review. Search for articles using the ProQuest and Google Scholar databases. The inclusion criteria for this study were articles published between 2016-2024, full text and open access articles, not in the form of a literature review. Research Results: The result found that from 10 articles, the majority came from Indonesia, 7 articles and 3 articles from Iran. There were 5 articles in Indonesian and 5 in English. The results of the study showed that educational interventions had an effect on patient self-efficacy in 5 articles, educational interventions had an effect on IDWG control in 4 articles. Conclusion: Educative intervention can increase self-efficacy and it maintains IDWG on CKD Patients